ANALISIS PERBANDINGAN TINGKAT PEMAHAMAN MAHASISWA TERHADAP ELEMEN LAPORAN KEUANGAN BERDASARKAN LATAR BELAKANG PENDIDIKAN MAHASISWA AKUNTANSI UNIVERSITAS PEKALONGAN - SE., M.Si, Syafnita (STIE Muhammadiyah Pekalonga, 2011)
This study purpose to improved empirically about differences of understanding and comprehension of student come from SMK Accounting, IPS High school,IPA High School and Madrasah Aliyah of element Financial Report (Balance Sheet)used as variable are; Asset, Liabilities, and Capital. Sample in this study are 83 students majoring in Accounting Â Universitas Pekalongan has completed the introductory course in accaunting 1 and 2. Uses different test Kruskal Wallis result show that there 2 variable asset and capital which claimed a significant difference between student from SMK Accounting, IPS High School, IPA High School dan Madrasah Aliyah. Variable Liabilities showed no significant. The result of the mean rank, all variable; asset,liabilities, and capital showed that students from SMK Accounting has higest mean rank value.Keywords; Asset, Liabilities, Capital and Accounting Students